Mortality, healthcare resource utilization, and cost among Medicare beneficiaries with Clostridioides difficile infection with and without sepsis. (April 2022) - Amin, Alpesh; Nelson, Winnie W.; Dreyfus, Jill; Wong, Anny C.; Mohammadi, Iman; Teigland, Christie; Dahdal, David N.; Feuerstadt, Paul
Objective: To describe mortality, healthcare resource utilization (HRU), and costs among Medicare beneficiaries with primary Clostridioides difficile infection (pCDI) or recurrent CDI (rCDI), with and without sepsis. Methods: We conducted a retrospective observational study of 100% Medicare Fee-for-Service claims from adults aged ⩾ 65 years with ⩾1 CDI episode between 1 January 2009 and 31 December 2017. Patients were continuously enrolled in Medicare Parts A/B/D 12 months before and up to 12 months after pCDI. ICD-9/10 codes defined CDI using ⩾1 inpatient claim, or ⩾1 outpatient claim plus ⩾1 claim for CDI treatment. The pCDI episode ended after 14 days without a CDI claim. rCDI episodes started within 8 weeks from the end of a previous CDI episode. ICD-9/10 codes identified all-cause sepsis over 12 month follow-up. Results: Of 497, 489 CDI patients, 41.0% ( N  = 203, 888) had sepsis; 57.7% with sepsis died versus 32.4% without sepsis. Among patients with pCDI only ( N  = 345, 893) or ⩾1 rCDI ( N  = 151, 596), 39.2% and 45.1% suffered sepsis, respectively. All-cause hospitalizations were frequent for all cohorts (range: 81–99%). Among patients who died, those with sepsis versus without had more-frequent intensive care unit (ICU) use (pCDI: 29% versus 15%; rCDI: 65% versus 34%), longer hospital stays (pCDI: 12 versus 10 days; rCDI: 12 versus 9 days), and higher per-patient-per-month costs (pCDI: $34, 841 versus $22, 753; rCDI: $42, 269 versus $25, 047). In both cohorts, sepsis patients who survived had higher total costs and all-cause HRU than those without sepsis. All p  < 0.001 above. Conclusions: Sepsis was common among Medicare beneficiaries with CDI. CDI patients with sepsis, especially after an rCDI, experienced higher mortality, HRU, and costs compared with those without sepsis.